1998
DOI: 10.1161/01.str.29.12.2507
|View full text |Cite
|
Sign up to set email alerts
|

Factor V Leiden Mutation Is a Risk Factor for Cerebral Venous Thrombosis

Abstract: Background and Purpose-Different coagulation disorders have been associated with cerebral venous thrombosis (CVT).Until now, fewer than 50 patients have been reported with CVT and the factor V Leiden (FVL) mutation. Although the prevalence of FVL-positive patients with CVT ranged from 10% to 25%, it was as low as 0.5% to 3% in the control groups. Most other studies had not systematically searched for concomitant risk factors or previous thromboembolic events. To better define the relevance of the FVL mutation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
1
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(57 citation statements)
references
References 32 publications
4
50
1
2
Order By: Relevance
“…2 With these same study samples we could detect a significant association of CVT with inherited variants in Factor XII and Factor II and confirmed the association with the factor V Leiden mutation 4 that was described by others before. 5 At an earlier occasion we pointed out that the genotypes found in the control population by Voetsch et al 1 are different from those reported by others for other white samples. 3 The use of these population data might have introduced a bias in their study.…”
Section: To the Editormentioning
confidence: 53%
“…2 With these same study samples we could detect a significant association of CVT with inherited variants in Factor XII and Factor II and confirmed the association with the factor V Leiden mutation 4 that was described by others before. 5 At an earlier occasion we pointed out that the genotypes found in the control population by Voetsch et al 1 are different from those reported by others for other white samples. 3 The use of these population data might have introduced a bias in their study.…”
Section: To the Editormentioning
confidence: 53%
“…Hormonal contraception is used by more than 100 million women throughout the world. Shortly after its introduction in the 1960s oral contraception (OC) was linked to an increased incidence of thrombovascular disease 16,17,18 This is mediated by its effects on the haemostatic system. Procoagulation activity caused by increased activity of coagulation factors VII, X and fibrinogen is a common finding in almost all preparations 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Of the 17 studies included, 16 were written in the English language [21][22][23][24]26,[29][30][31]35,[37][38][39]41,43,45,46 and 1 in the Chinese language. 32 All included studies were case-control studies.…”
Section: Study Characteristicsmentioning
confidence: 99%